Neuroanatomy and neuroscience at a glance - Barker, Roger A. , 1961-; Cicchetti, Francesca; Neal, M. J. (At a glance series, 2012)
Neuroanatomy and Neuroscience at a Glance provides a user-friendly introduction to the anatomy, biochemistry, physiology and pharmacology of the human nervous system within one, succinct, highly-illustrated volume